Impact of Trade Policy Reforms on the Environment - Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2001)
The paper attempts to provide a theoretical analysis as well as some indicators on the linkage between trade policy and the environment. It looks at what has happened to the share of manufacturing industries by pollution classification over time and finds that the share of non-pollutive/nonhazardous industries have grown over the years covering the period of trade reforms. The impact of trade policy on the environment was also analyzed using a simulation model which predicts what happens to pollution intensity with and without trade reforms. The results indicate some positive impact of trade reforms on the environment and the findings suggest that the Philippines should pursue its current thrust towards greater trade liberalization and implement the corresponding environmental measures.
Keywords: 330; trade reforms; pollution; environmental issues; trade policies; Außenwirtschaftspolitik; Handelsliberalisierung; Umweltbelastung; Philippinen